The protective effect of icariin and phosphorylated icariin against LPS-induced intestinal goblet cell dysfunction - Xiong, Wen (Innate Immun, 2019)
In this study, we used LS174T cells as a model to investigate the protective effects of icariin and phosphorylated icariin on LPS-induced goblet cell dysfunction. Our results indicated that icariin and phosphorylated icariin increased the cell viability and decreased lactate dehydrogenase activity in LPS-treated LS174T cells. Icariin and phosphorylated icariin attenuated LPS-induced changes in mucin 2 synthesis and secretion. Besides, Icariin and phosphorylated icariin reduced the levels of ROS, MDA, and H(2)O(2) and increased the activity of SOD, GPx, CAT, and T-AOC in LPS-treated LS174T cells. Moreover, the levels of IL-1β, IL-6, IL-8, and TNF-α were reduced in the Icariin and phosphorylated icariin group. Furthermore, Icariin and phosphorylated icariin decreased gene abundance or enzyme activity of Bip, XBP1, GRP78, CHOP, caspase-3, and caspase-4 in LPS-treated LS174T cells. Our data suggest that Icariin and phosphorylated icariin effectively attenuate LPS-induced intestinal goblet cell function damage through regulating oxidative stress, inflammation, apoptosis, and mucin expression.